Guiding of relativistic electron beams in dense matter by laser-driven magnetostatic fields - M. Bailly-Grandvaux (Nature Portfolio, 2018)
Efficient energy transport by laser-driven relativistic electron beams is crucial in many applications including inertial confinement fusion, and particle acceleration. Here the authors demonstrate relativistic electron beam guiding in dense plasma with an externally imposed high magnetic field.